Correlation Between Predictor Factors (Hemoglobin, Leukocytes, Platelets, LDL, HbA1c, D-dimer, Albumin) and Length of Stay in Patients with Diabetic Ulcers at Dr. Pirngadi General Hospital Medan, 2022–2023 - Hotlin Cantika Nainggolan; Bastanta Tarigan; Novrina Situmorang; Maestro Simanjuntak; Batara Simangunsong (Jurnal Kedokteran Methodist, 2025)
Background : Uncontrolled diabetes causes chronic complications, both microangiopathies and angiopathies. Diabetic ulcers are one of the chronic complications of diabetes, caused by macroangiopathy resulting in vascular insufficiency and neuropathy. Ulcers are a concern which will lead to a level of disability that will prolong the patient’s treatment period. Factors that affect the length of care in diabetic ulcer patients are metabolic control (poor blood sugar, hba1c, albumin, hemoglobin, LDL, LDL), infection control (elevated leukocytes), vascular control (increased d-dimer coagulation). The length of treatment of diabetic ulcer patients will burden both the patient and the state. Research: To analyze the relationship of predictor factors (hemoglobin, leukocytes, platelets, LDL, HbA1c, D-dimer, Albumin) to the length of treatment of diabetic ulcer patients at Dr. Pirngadi Hospital Medan City. Methods: This study is an analytic observational study with a research design using a cross-sectional study. Results: Based on the results of the proportion test with the Chi- square correlation test there is a relationship between hemoglobin (p- value of 0.008), the relationship between leukocytes (p-value of 0.010), the relationship between platelets (p-value of 0.010), the relationship between LDL (p-value of 0.047), the relationship between HbA1C (p-value of 0.046), the relationship between D-dimer (p-value of 0.025), the relationship between albumin (p-value of 0.041) with the length of treatment of diabetic ulcer patients. In multivariate results, the factor that most influences the length of treatment is leukocytes. Conclusion: Hemoglobin, leukocyte, platelet, LDL, HbA1c, D-dimer, Albumin levels are factors associated with the length of treatment of diabetic ulcer patients at Rsud Dr. Pirngadi Medan City in 2022-2023 and leukocytes are the most influential factor. Keywords: diabetes, diabetic ulcer, length of stay